2021
DOI: 10.3390/met11111674
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of MQL and Dry Environments on Tool Wear, Cutting Temperature, and Power Consumption during End Milling of AISI 1040 Steel

Abstract: Minimum quantity lubrication (MQL) is a sustainable method that has been efficiently applied to achieve machinability improvements with various materials in recent years, such as hardened steels, superalloys, soft metals, and composites. This study is the first to focus on the performance evaluation of MQL and dry milling environments with AISI 1040 steel. The tool wear, cutting temperature, and power consumption were considered as the quality responses while cutting speed, feed rate and machining environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 51 publications
0
21
0
1
Order By: Relevance
“…The samples were machined under dry and MQL conditions because today's manufacturing industry is very much focused on environmental protection [47] and a reduction in the consumption of machining fluids [48]. Furthermore, MQL has been successfully applied to improve the machinability of difficult-to-cut materials [49,50]. In the MQL method, we used ECOCUT MIKRO 20 E oil, which was produced by mixing with air.…”
Section: Workpiece Details and Preparationmentioning
confidence: 99%
“…The samples were machined under dry and MQL conditions because today's manufacturing industry is very much focused on environmental protection [47] and a reduction in the consumption of machining fluids [48]. Furthermore, MQL has been successfully applied to improve the machinability of difficult-to-cut materials [49,50]. In the MQL method, we used ECOCUT MIKRO 20 E oil, which was produced by mixing with air.…”
Section: Workpiece Details and Preparationmentioning
confidence: 99%
“…Satur et al [92] used a 240 × 180 pixel infrared camera by Testo company, to investigate the effects of MQL and dry environments during the end milling of AISI 1040 steel on cutting temperature, tool wear and power consumption. The thermal camera was positioned approximately 50 cm from the cutting zone and considered only the peak temperature values pixel by pixel from the interface.…”
Section: Infrared Camerasmentioning
confidence: 99%
“…Experimental results show that feed rate, tool speed and cutting depth are of different importance in generating surface roughness and surface hardness [ 22 ]. Salur et al studied the influence of MQL and dry conditions on the end milling process, and found that the cutting environment had the greatest influence on power consumption, while cutting speed had an important influence on tool wear [ 23 ].…”
Section: Introductionmentioning
confidence: 99%